Chronic Conditions, Persistent Pain, and Psychological Distress Among the Rural Older Adults: A Path Analysis in Shandong, China - Yang, Shijun; Li, Jie; Zhao, Dan; Wang, Yi; Li, Wenjuan; Li, Jie; Li, Zhixian; Wei, Zhen; Yan, Chen; Gui, Zhen; Zhou, Chengchao (Frontiers in Medicine, 2021)
Psychological distress were found to be associated with chronic conditions and persistent pain. However, few studies explored the underlying pathways between them. This study aimed to analyze the path of chronic conditions and persistent pain on psychological distress through sleep quality and self-rated health. A total of 2,748 rural older people in Shandong, China were included in this study. Path analysis was performed by using Mplus 8.3 to examine the associations between chronic conditions, persistent pain, sleep quality, self-rated health, and psychological distress after adjusting for age, gender, education, and household income. The prevalence of psychological distress among the older adults in this study was 47.49%. Chronic conditions and persistent pain were indirectly associated with psychological distress through six mediating pathways: (1) the path from chronic conditions to psychological distress through sleep quality (β = 0.041, 95%CI: 0.015 - 0.067) and self-rated health (β = 0.064, 95%CI: 0.038 - 0.091) respectively, and a chain mediation existed (β = 0.007, 95% CI: 0.000 - 0.014); (2) the path of persistent pain and psychological distress through sleep quality (β = 0.058, 95% CI: 0.014 - 0.102) and self-rated health (β = 0.048, 95% CI: 0.000 - 0.096) respectively, also the chain mediation found (β = 0.009, 95% CI: 0.005 - 0.014). Psychological distress was associated with chronic conditions and persistent pain through decreased sleep quality and self-rated health among Chinese rural older people. Multi-pronged targeted intervention should be taken for older adults with chronic conditions and persistent pain.